Cobalt(II) complexes of tetraazamacrocycles derived from b-diketones and diaminoalkanes - R. N. PRASAD; MITHLESH AGRAWAL; SANJNA SHARMA; SMILJANA RAICEVIC (Journal of the Serbian Chemical Society, 2005)
Co(II) complexes of the type [Co(L)(NO3)2] (L = tetraazamacrocycle with 18 to 34-membered ring) were synthesized by the template condensation of b-diketones, such as 2,4-pentanedione, 1-phenyl-1,3-butanedione or 1,3-diphenyl-1,3-propanedione, with diaminoalkanes. The complexes were characterized by elemental analyses, molar conductances and magnetic moments measurements, as well as infra red and electronic spectroscopy.